Kraton Buton sebagai Sumber Sejarah Lokal dalam Pembelajaran Sejarah - Ali Guntur (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2018)
The focus of this research is Kraton Buton as a source of local history in history learning. This study describes or describes the Kraton Buton as an ancestral heritage of the Buton Sultanate which has a beautiful and majestic place and has civilization and cultural values ​​that historians need to exploit as a source of local history, in order to foster students' awareness of their local history and culture. Data search is done through observation, interview and documentation. The methodology used is qualitative with Miles and Huberman interactive analysis model approach that is data reduction, data presentation, and conclusion, to browse and uncover the facts. The result of this research is Kraton Buton as the former government center of Buton Sultanate and as the center of Buton culture keeps unique and interesting relics. The management effort of the palace area in 2003 by the Baubau City government through the Tourism Department opened the space for Kraton Buton to be used as a source of local history by the public widely including for scientific research purposes. The opening of Kraton Buton also encourages the role of history teacher to utilize Kraton Buton as a source of local history in learning history in class. Fokus penelitian ini adalah Kraton Buton sebagai sumber sejarah lokal dalam pembelajaran sejarah. Penelitian ini mendeskripsikan atau menggambarkan Kraton Buton sebagai warisan leluhur Kesultanan Buton yang memiliki tempat yang indah dan megah dan memiliki peradaban serta nilai-nilai budaya yang perlu untuk dimanfaatkan oleh guru sejarah sebagai sumber sejarah lokal, agar dapat menumbuhkan kesadaran siswa atas sejarah dan budaya lokalnya. Pencarian data dilakukan melalui observasi, wawancara dan dokumentasi. Metodologi yang digunakan adalah kualitatif dengan pendekatan model analisis interaktif Miles dan Huberman yaitu reduksi data, penyajian data, dan penarikan kesimpulan, untuk menelusuri dan mengungkap fakta tersebut. Hasil penelitian ini adalah Kraton Buton sebagai bekas pusat pemerintahan Kesultanan Buton dan sebagai pusat kebudayaan Buton menyimpan peninggalan-peningalan yang unik dan menarik. Upaya pengelolaan wilayah kraton pada tahun 2003 oleh pemerintah Kota Baubau melalui Dinas Pariwisata membuka ruang bagi Kraton Buton untuk dijadikan sebagai sumber sejarah lokal oleh masyarakat secara luas termasuk untuk keperluan penelitian karya ilmiah. Terbukanya Kraton Buton ini pula mendorong peran guru sejarah untuk memanfaatkan Kraton Buton sebagai sumber sejarah lokal dalam pembelajaran sejarah di kelas.